Analisis Kebangkrutan Perusahaan dengan Menggunakan Metode Z Score (Studi Kasus pada Industri Consumer Goods di Bursa Efek Jakarta Periode 1997 – 2000) - Nuning Kriesnawati; Rita Kusumawati (Journal of Accounting and Investment, 2003)
This study aimed to analyze bankruptcy using the Z score. Research done in the consumer goods industry listed in Jakarta Stock Exchange 1997-2000 period. The results found that in 2000 the value of Z score companies has decreased, this is possible because the value of the variable X3 and X4 has decreased, but in 2001 the value of Z score Integration again experienced an increase, although not as high as in 1999, this means that the company can improve its performance. PT Mandom value of Z score indicates that the company is in a good condition or not bankruptcy. Z score value of the company from 1997 to 2001 continues to increase, it suggests that good corporate performance which proved that despite the crisis the company was still able to survive even continue to increase. Analysis of the bankruptcy of PT Unilever shows that the company is in a good condition. As in PT Mandom, the company is also not affected by the crisis. Z score value of the company from 1997 to 2001 have increased constantly, this indicates that the performance is good. Analysis of the bankruptcy of the PT Procter and Gamble shows that the company is in conditions that are less stable, this is indicated by the value of Z score in 1997 shows that the company is in the condition of the gray area, in 1998 based on assessment standards of bankruptcy, the company in 1998 experienced bankruptcy, in 1999 the company experienced a slight improvement from the beginning in a state of bankruptcy changes on the condition of the gray area, in 2000 the company was in good condition or not bankrupt, this is possible because the company sells most of its fixed assets in order to operate properly. However, in 2001 the company back on the condition of the gray area, it is because the value X2 to X5 has decreased.